2012
DOI: 10.1136/annrheumdis-2012-201397
|View full text |Cite
|
Sign up to set email alerts
|

The US7 score is sensitive to change in a large cohort of patients with rheumatoid arthritis over 12 months of therapy

Abstract: PurposeTo determine the sensitivity to change of the US7 score among RA patients under various therapies and to analyze the effect of each therapeutic option over 1 year. To estimate predictors for development of destructive bone changes.MethodsMusculoskeletal ultrasound (US7 score), DAS28, CRP and ESR were performed in 432 RA patients at baseline and after 3, 6 and 12 months. The cohort was divided into four sub-groups: first-line DMARDs (Group 1; 27.3%), therapy switch: DMARDs to second DMARDs (Group 2; 25.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 19 publications
(19 reference statements)
1
56
0
7
Order By: Relevance
“…Another study found that US synovitis score in 7 joints (US 7) was a better tool of assessing disease activity than composite disease activity scores in patients with RA and associated FM. The PD US7 score correlated with DAS28 only in patients without FM [17]. Our findings show small correlation coefficients between GS US and DAS28 and moderate for PD US and DAS28, suggesting that PD US could perform better in assessing disease activity in patients with RA and associated FM.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Another study found that US synovitis score in 7 joints (US 7) was a better tool of assessing disease activity than composite disease activity scores in patients with RA and associated FM. The PD US7 score correlated with DAS28 only in patients without FM [17]. Our findings show small correlation coefficients between GS US and DAS28 and moderate for PD US and DAS28, suggesting that PD US could perform better in assessing disease activity in patients with RA and associated FM.…”
Section: Discussionmentioning
confidence: 55%
“…Wrists and MCP joints were examined in the longitudinal plane, from the dorsal aspect and PIP joints from the volar aspect to assess the presence of synovial fluid/ hypertrophy (GS) and synovial vascularisation (PD) (1 scan each joint). Compartment 6 of the dorsal wrist (extensor ulnari carpis tendon) and 1-5 finger flexor tendons were scanned for the detection of tenosynovitis (TS) in GS and PD US [17] in both hands. A total of 12 tendons were scanned for the detection of TS.…”
Section: Ultrasound Examinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Long term studies (>1 year) are few [113]. Statistical significance was obtained only at 30-38 weeks due to the low patients number included in the studies [117,118].…”
Section: Follow Up Frequencymentioning
confidence: 99%
“…Currently, grade I synovitis is considered nonspecific for RA, being present in about 15% of the controls and without therapeutical relevance according to some authors opinion [114]. Indeed, a low PD grade associated to GS grade I may not necessarily reflect active synovitis [117]. On the contrary, according to a recent published study, GS grade I synovitis is not encountered in healthy subjects [122].…”
Section: Grey Scale -Grade I Synovitismentioning
confidence: 99%